Isoprenoid-Derived Metabolites and Sugars in the Regulation of Flowering Time: Does Day Length Matter? - Gawarecka, Katarzyna; Ahn, Ji Hoon (Frontiers in Plant Science, 2021)
In plants, a diverse set of pathways regulate the transition to flowering, leading to remarkable developmental flexibility. Although the importance of photoperiod in the regulation of flowering time is well known, increasing evidence suggests the existence of crosstalk among the flowering pathways regulated by photoperiod and metabolic pathways. For example, isoprenoid-derived phytohormones (abscisic acid, gibberellins, brassinosteroids, and cytokinins) play important roles in regulating flowering time. Moreover, emerging evidence reveals that other metabolites, such as chlorophylls and carotenoids, as well as sugar metabolism and sugar accumulation, also affect flowering time. In this review, we summarize recent findings on the roles of isoprenoid-derived metabolites and sugars in the regulation of flowering time and how day length affects these factors.